Konsep Literasi Digital dalam Kurikulum Merdeka Belajar pada Era Disrupsi di Sekolah Dasar: Kajian Buku “Literasi Digital dalam Dunia Pendidikan di Abad ke-21” Karya Daniel Ginting - Lupita Atika Rachma (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2025)
The era of disruption is marked by the rapid development of ICT, education is required to adapt through a change in mindset from a fixed mindset to a growth mindset in order to create effective, efficient, and relevant learning. The use of ICT in schools, such as e-report cards and digital-based learning has become a necessity in line with the demands of generation Z and alpha who are growing up in a digital environment. However, major challenges are still faced, especially the low digital literacy of teachers and students which has an impact on the quality of learning. Digital literacy, which includes technical skills, critical thinking, and responsible use of digital media, needs to be strengthened through training and integration in the independent curriculum. The book